Clinico-epidemiological profile of orofacial clefts among children of coastal district of Southern India: A 5 year hospital based study - Supriya Nambiar; Prateek Singhal; Anand Menon; B Unnikrishnan (Wolters Kluwer Medknow Publications, 2014)
Background: In India with a large multi ethnic population, most of the epidemiological studies on cleft lip/palate (CL/P) have been sporadic. Inequalities exist, both in access to and quality of cleft care with distinct differences in urban versus rural access and over the years the accumulation of unrepaired clefts of the lip and palate make this a significant health care problem in India. Aims and Objectives: The primary aims of this study was to assess the predominant pattern of cleft lip and palate (CLP) cases in Mangalore and secondary aim is to evaluate the role of possible risk factors like previous familial history, maternal diet and nutritional supplementation, consanguinity. Materials and Methods: This was a 5-year hospital based, retrospective study of the birth records, in which all the cases of CL/P up to the age group of 5 years were studied. The data was retrieved from the Medical Records Department of two main hospitals in Mangalore. The data was collected using a semi-structured, pre-tested proforma that was designed based on the review of literature. Results: The cleft occurrence in Mangalore was found to be 2.42/1000 births/year. Cleft lip (CL) along with cleft palate (CP) was found to be the highest in both Hospitals about (64.6%), followed by isolated CL (28.5%), followed by isolated CP (5.1%) and the least being isolated CL with cleft alveolus (1.9%). Conclusions: From the study, it can be concluded that recording of adequate ante-natal history in the birth records hasn't been given critical Importance. Furthermore, there is a lack of parental counseling provided in the government hospital.